Elt Praxis In Intercultural Context: Ensb Pre-service Teachers’ Perceptions Of Program Adequacy & Preparedness For Cultural Integration - Selama, Sid Ali (The Journal of Studies in Language, Culture, and Society, 2025)
Intercultural communicative competence, as an area of study, continues to intrigue teachers, researchers and teaching/learning materials designers; thus, much has been written on the subject. In Algeria and abroad, literature on foreign languages education has always served to disseminate information on and ideas for developing learners’ intercultural communicative competence. However, little research on the place of culture in EFL teacher education programs may be found. This paper, therefore, attempts to discover whether the current EFL teacher training programs in Algeria effectively prepare future teachers to deal with culture in their classrooms. Failure to address this issue risks neglecting critical aspects of teacher preparation and, by extension, the credibility of teacher education as an area of study will be undermined. To fill this research gap, we opted to examine the extent to which initial training for teachers in Algeria can foster learners’ intercultural communicative competence. The researcher achieved this by 1) reviewing the teacher knowledge base identified as essential in literature related to teacher education, and 2) addressing a range of quality indicators, including future EFL teachers’ sense of preparedness for integrating intercultural communicative competence into their lessons. Using a quantitative research design, data were collected through a structured questionnaire consisting of Likert-scale items. The sample included 34 pre-service teachers enrolled at the Ecole Normale Supérieure Bouzereah, Algiers, Algeria. The collected data were analyzed using descriptive statistics through SPSS to identify patterns in participants’ responses. The findings revealed that although participants acknowledged the importance of integrating cultural elements into language teaching and felt moderately prepared for intercultural communicative competence, gaps seemed to be persistent in practical application, highlighting the need for more targeted training in culturally responsive pedagogy. Based on the findings, it is recommended that teacher education programs provide more practical, experience-based training to support the development of intercultural communicative competence.